Advancements and future perspectives in nutrient film technique hydroponic system: a comprehensive review and bibliometric analysis - Palmitessa, Onofrio Davide; Signore, Angelo; Santamaria, Pietro (Frontiers in Plant Science, 2024)
In the context of climate change, reducing the environmental impact of agriculture has become increasingly critical. To ensure sustainable food production, it is essential to adopt cultivation techniques that maximize resource efficiency, particularly in water and nutrient usage. The Nutrient Film Technique (NFT) is one such hydroponic system, designed to optimize water and nutrient use, making it a valuable tool for sustainable agriculture. This bibliometric review examines the evolution of NFT research from 1977 to 2023, focusing on the growing interest in this method as a solution to the agricultural challenges posed by climate change. Through the analysis of 774 scientific documents, this review highlights an upward trend in NFT-related studies, with a noticeable shift from conference proceedings to peer-reviewed journal articles, particularly in recent years. Acta Horticulturae has been a leading journal in this field, underscoring the significance of early conference contributions. Lettuce and tomatoes have emerged as the primary crops studied in NFT systems, demonstrating the technique’s broad applicability. Research on lettuce has primarily focused on nitrate accumulation and biofortification, aiming to improve both the nutritional quality and safety of the crop. Studies on tomatoes have explored challenges related to oxygen concentration in the nutrient solution, where innovations such as the Nutrient Drip Technique (NDT) and the New Growing System (NGS) have shown promise in addressing these issues. Other key areas of NFT research include the effects of water salinity on crop growth and the integration of NFT with aquaponics systems, highlighting its potential for sustainable, water-efficient crop production. However, challenges such as nutrient imbalances and disease management persist. This review underscores the growing relevance of NFT in the pursuit of environmentally sustainable agriculture. Continued innovation and research are essential to optimizing nutrient management, refining environmental controls, and exploring new crop varieties, thereby enhancing the potential of NFT for sustainable farming systems.